Rancang Bangun My temp (alat pendeteksi suhu badan berbasis IOT) - Muhammad, Nauval Arkan Aunillah; Nurpulaela, Lela (Peneliti.net, 2024)
Design and Development of My Temp (IoT-Based Body Temperature Monitoring Device). This research aims to design and develop a body temperature detection device based on the Internet of Things (IoT) called